Roles of Salespersons on Stayers and Defectors in Taiwan Tourism - Liang, Chih-Chin; Trong, Le Duc (Xing Xiao Ping Lun, 2018)
Customer loyalty is conventionally measured in terms of its effects on repurchase intention but not in terms of its effects on actual loyalty behavior. Repurchase intention is also a widely used surrogate for actual loyalty behavior but little research has demonstrated that repurchase intention can accurately predict customers who will stay or defect. This study analyzed four elements of "actual loyalty behavior" that determines whether a tourist visiting Taiwan is likely to stay or defect: value creation, relationship development, customer satisfaction and service quality. Identifying actual loyalty behavior through stayers is important in establishing a deeper understanding of customer loyalty and it can be helpful for Taiwan tourism. The subjects of the study were 659 Taiwanese residents who had travel experience. The analytical results revealed the differences between stayers and defectors. The implications of this study are also discussed.